Organizational Learning at Islamic Boarding School In Entering Global Era - Umar Sidiq (Al-Hayat: Journal of Islamic Education, 2017)
Islamic Boarding School leadership no longer applies a single leadership pattern in the form of legal entity. With such leadership pesantren become one of the modern educational institutions. Learning Organization is a tool to build a quality organization or foundation. Every member of the organization needs to continuously develop its capabilities for future improvement. Development of organization and skill of its members.